Isolated cysticercosis of masseter muscle in a young boy with trismus: Report of a case misdiagnosed as unilateral temporomandibular joint ankylosis - Jyoti Prajapat; Rajesh Prajapat; Puneeta Vohra (Wolters Kluwer Medknow Publications, 2019)
Cysticercosis is a parasitic infection caused by the larval stages of Taenia solium. Cysticercosis is a potentially fatal parasitic disease that was rarely found in the maxillofacial region. This report suggests that cysticercosis should be considered in the differential diagnosis of chronic swelling in the oral and maxillofacial region and the importance of noninvasive modality ultrasonography (USG) in diagnosis. This paper reports a case of cysticercosis in the right masseter muscle in an 11-year-old boy who presented with recurrent swelling on the right side of the face with inability to open mouth, its clinical features, diagnostic modalities used, and management of the case. Cysticercosis should be considered in the differential diagnosis of chronic oral and maxillofacial swelling. High-resolution USG is an excellent noninvasive and cost-effective modality for the diagnosis and also suggests that this parasitic infection can be successfully treated with conservative management using antihelminthic medication.